Achievement and Improvement of the Ability of Mathematical Understanding and Self Confidence of 5th Grade Students at Cooperative Learning Type Think Pair Share - Ervin Reliavirli Rusti (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The research aims to obtain an overview of the achievement and improvement of the ability of mathematical understanding and self-confidence of students in learning with the cooperative model type think pair share and direct learning. The method in this research is quasi experiment with pretest-posttest non equivalent groups design. The subject of this research was the fifth grade students of one of the elementary schools in Cidahu, Sukabumi. The result of the research, it can be concluded that based on the average (1) there are differences in the achievement and the increase of mathematical comprehension ability between students who get learning with the cooperative model type think pair share and students who get direct learning (2) There are differences in achievement and the increase of self confidence between students who get learning with the cooperative model type think pair share and students who get direct learning.